PENGARUH LOKASI USAHA DAN INOVASI TERHADAP KEBERHASILAN USAHA PADA USAHA KULINER PECEL LELE DI KECAMATAN BATURAJA TIMUR (Ekonomika, 2022)
This reseacrh discussed the influence of Business Location and innovation on businees success This reseacrh discussed the Influence of Business Location and Innovation on Business Success in Catfish Pecel Culinary Business in East Baturaja District. The population in this study was 31 businessmen of catfish pecel in East Baturaja District. The data analysis method used was quantitative method using Multiple Linear Regression analysis tool. The results of the analysis explained that the t-count of each Business Location variable (X1) is 3.154 and Innovation (X2) was 3.932 which was greater than the t-table value of 2.04841 which stated that all variables had a significant influence on Business Success in Catfish Pecel Culinary Business in the District of East Baturaja. Simultaneously, it was found that there was an influence of Business Location and Innovation on Business Success in Catfish Pecel Culinary Business in East Baturaja District. The calculated F value of 56.975 was greater than the F table of 3.34 which stated that together Business Location and Innovation had a significant influence on Business Success in the Catfish Pecel Culinary Business in East Baturaja District. The value of the coefficient of determination (R2) was 0.803. this showed that the contribution of the influence of business location and innovation to business success was 80.3% while the remaining 19.7% was influenced by other variables outside this study, namely motivation, competence and so on (Noor. 2017:401).